Tuning d‐Band Structure of CuII in Coordinated Polymer via d–π Conjugation for Improving CO2 Electroreduction Selectivity toward C2 Products. Issue 19 (1st September 2022) - Zhang, Fengtao; Wang, Peng; Zhao, Runyao; Wang, Yiding; Wang, Jianji; Han, Buxing; Liu, Zhimin
Abstract: Copper‐coordinated catalysts are reported to be effective for electrocatalytic CO2 reduction reaction (CO2 RR) to C2 products but suffer from low selectivity. Herein a strategy was developed to tune the d‐band structure of Cu II via coordinating with aromatic ligands to form Cu‐based conjugated polymers for CO2 RR to C2 chemicals. The catalysts derived from copper chloride coordinating with tetraminobenzoquinone (TABQ) and with 1, 2, 4, 5‐benzenetetramine possessed high‐density and compact Cu single‐atom sites and displayed high activity for CO2 RR to C2 products. Especially, Cu‐TABQ exhibited a maximum C2 faradaic efficiency of 63.2 % with a current density of 423 mA cm −2 at −1.17 V (vs. reversible hydrogen electrode). Density functional theory calculations indicated that the TABQ linker possessing C=O groups significantly widened the d‐band of coordinated Cu II, which facilitated binding of *CO intermediate on the catalyst and thus enhanced C−C coupling. This work provides mechanistic insight into the Cu II ‐coordinated polymers for CO2 RR with high selectivity toward C2 products. Abstract : CO2 reduction : Tuning the d‐band structure of Cu II center via tetraminobenzoquinone (TABQ) linker with C=O groups regulates the binding energy of electrocatalytic CO2 reduction reaction (CO2 RR) intermediates on the catalyst and significantly improves the selectivity towards C2 products, resulting in the highest C2 faradaic efficiency (63.2 %) for CO2 RR among metal‐coordinated or single‐atom catalysts.